Pengukuran Kepuasan Pengguna pada Website Dicoding Menggunakan Metode EUCS - Tiohandra, Mufadha; Subiyakto, A’ang (P3M Politeknik Negeri Banjarmasin, 2024)
Education is the basic right of every person and the current era of digitalization has increased access to education through the availability of the internet. Nowadays, education is not only limited to formal school channels where one has to go somewhere to receive education, but it can be done anywhere and anytime with the help of online platforms. One of the certified online learning platforms is Dicoding which provides training and materials in information technology, particularly in programming. Dicoding allows its users to improve their skills and knowledge in an interactive and self-directed way using a variety of available content related to the industry. In assessing the quality of the service provided, measures such as the End User Satisfaction Method (EUCS) are used which focuses on user satisfaction with content, accuracy, ease of use, aesthetics, and timeliness. As a result, users rated the service Under Review, i.e., better than they expected and they were able to achieve their learning outcomes with good satisfaction.